(untitled) - Pence, Gregory E. (Boston, Mass., 2004)
This rich collection, popular among teachers and students alike, provides an in-depth look at major cases that have shaped the field of medical ethics. The book presents each famous (or infamous) case using extensive historical and contextual background, and then proceeds to illuminate it by careful discussion of pertinent philosophical theories and legal and ethical issues.
Keywords: Đạo đức y học,Medical ethics